More than a feeling? Impact of face masks on cardiorespiratory parameters and microclimate under the mask in school-aged children - Eike-Maximilian Marek; Adriana Talarico; Vera van Kampen; Thomas Behrens; Birger Jettkant; Susann Widmer; Frank Hoffmeyer; Nelly Otte; Anna Hoffmann; Anne Schlegtendal; Folke Brinkmann; Benjamin Kendzia; et al. (Building and Environment, 2026)

Ecology and mechanisms of brood raiding of Iridomyrmex by the thermophilic ant, Melophorus anderseni - Benjamin D. Hoffmann; Sara Hu; Adrian A. Smith; Andrew V. Suarez; Terry McGlynn (Insectes Sociaux, 2026)
Melophorus anderseni is a thermophilic ant species that nests near colonies of Iridomyrmex on which it conducts brood raids. We examined its colony founding behavior and foraging ecology to evaluate possible mechanisms that may facilitate interspecific nest raiding, as well as determine if it is a parasite or specialist predator. Specifically, we (1) examined colony establishment and survival, (2) patterns of worker activity (walking speed, foraging and raiding behavior), and (3) compared cuticular hydrocarbon profiles of M. anderseni and I. reburrus workers. Following nuptial flights, M. anderseni queens established colonies in clusters around I. reburrus colonies, with an average distance to the nearest Iridomyrmex nest of 133.1(± 8.9) cm (range 25 to 650 cm). The average number of M. anderseni queens per Iridomyrmex nest entrance was 8.4 (± 1.9), and the average distance to the nearest M. anderseni neighbor was 44.9 (± 5.3) cm (range 10 to 233 cm). Queen survival was lower in clusters that were farther from the nearest I. reburrus nest or to other M. anderseni queens. Iridomyrmex reburrus activity was negatively related to soil temperature, with no activity occurring above 50 °C. In contrast, M. anderseni activity was positively related to temperature with peak activity occurring just above 50 °C. Melophorus anderseni worker activity commenced when soil temperatures exceeded 37.4 °C, and activity increased until mid-day. Activity ceased in the afternoon at temperatures lower than that for activity commencement, on average at 36.7 °C. Activity of M. anderseni at I. reburrus nests followed that of activity at M. anderseni nests. Workers of M. anderseni had an average foraging duration of 63 s and a mean foraging distance of 249 cm. Of the 49 foragers followed, 42 (86%) entered an I. reburrus nest, and 32 (76.2%) of those entered the closest nest entrance. Of the 1,444 observations of M. anderseni exiting an I. reburrus nest, they stole an item in 122 (8.4%) instances, with 117 (95.9%) of these items being brood. Additionally, workers of M. anderseni had faster running speeds (mean 9.72 cm/s, peak 18 cm/s) than I. reburrus workers (7.05 cm/s). On average, the speed of M. anderseni exiting an I. reburrus nest was more than twice the speed of I. reburrus. Extracts of I. reburrus and M. anderseni worker cuticular hydrocarbon profiles were qualitatively identical in that no compounds were unique to either species. Saturated hydrocarbons with chain lengths between 25 and 29 carbons comprised the majority of hydrocarbons found on the cuticle of both species. The relative abundances of compounds within the profiles of both species were also similar. In contrast, two sympatric Iridomyrmex and Melophorus species shared very few compounds with I. reburrus and M. anderseni . During all observations of the M. anderseni nests, no I. sanguineus workers were observed within or exiting the nest entrance, indicating that stolen brood had been consumed. Our results support that M. anderseni specializes on brood raiding from I. reburrus nests, and this raiding is for predation, not dulosis. Both behavior (running speed) and chemical mimicry are likely used in combination to facilitate this specialized foraging. Additional research is still needed to determine the source (e.g. genetic versus environmental) of M. anderseni’s hydrocarbon profiles, and if geographic variation in host use and chemical mimicry exists.

Submarine groundwater discharge into a temperate tidal basin: Mapping and characterization by a multi-method and multi-scale approach - Ercan Erkul; Tina Wunderlich; Dennis Wilken; Jan Igel; Mike Müller-Petke; Mathias Ronczka; Tobias Splith; Simon Fischer; Benjamin Gilfedder; Michael Ernst Böttcher; Cátia M. Ehlert von Ahn; Ralf Gründling; et al. (Estuarine, Coastal and Shelf Science, 2025)

Roles of researchers in inter- and transdisciplinary sustainability research: a reflection tool - Benjamin Hofmann; Hanna Salomon; Sabine Hoffmann (Sustainability Science, 2025)
Inter- and transdisciplinary (ITD) research is increasingly called for and supported to promote sustainable transformation through knowledge co-production, knowledge integration, and solution development. The paper explores what is needed to support researchers in reflecting on their new roles in ITD research. We introduce a reflection tool that makes the growing literature on researchers’ roles in sustainability science applicable to ITD projects. Its design is based on the arguments that each researcher can have several roles within one research project and that focusing on a few key roles increases clarity compared to differentiating many specialized roles. The tool consists of (1) a researcher survey that operationalizes six prominent roles (traditional scientist, self-reflexive scientist, knowledge integrator, knowledge broker, process facilitator, and change agent), (2) a visualization of role profiles from the survey, and (3) a set of reflection questions on related opportunities, challenges, and coping strategies on individual and project level. We empirically applied the tool in two ITD research projects focused on sustainable food production and water and forest ecosystem management. Comparative application of the tool yielded diverse role profiles of researchers in both projects, with different patterns for senior and junior researchers as well as natural and social scientists. The reflection produced a collection of opportunities, challenges, and coping strategies that corroborates and extends insights from ITD literature. We discuss how the tool triggers multi-dimensional reflection on roles (individual and project level, role combinations, self-perception and external perception) and outline opportunities for further strengthening such reflection in ITD research.

Towards better understanding the urban environment and its interactions with regional climate change - The WCRP CORDEX Flagship Pilot Study URB-RCC - Gaby S. Langendijk; Tomas Halenka; Peter Hoffmann; Marianna Adinolfi; Aitor Aldama Campino; Olivier Asselin; Sophie Bastin; Benjamin Bechtel; Michal Belda; Angelina Bushenkova; Angelo Campanale; Kwok Pan Chun; et al. (Urban Climate, 2024)

Environmental DNA methods for biosecurity and invasion biology in terrestrial ecosystems: Progress, pitfalls, and prospects - Karen L. Bell; Mariana Campos; Benjamin D. Hoffmann; Francisco Encinas-Viso; Gavin C. Hunter; Bruce L. Webber (Science of The Total Environment, 2024)

Fronto-striatal alterations correlate with apathy severity in behavioral variant frontotemporal dementia - Neeraj Upadhyay; Annika Spottke; Anja Schneider; Daniel C. Hoffmann; Ingo Frommann; Tommaso Ballarini; Klaus Fliessbach; Benjamin Bender; Hauke R. Heekeren; John Dylan Haynes; Michael Ewers; Emrah Düzel; et al. (Brain Imaging and Behavior, 2023)
Structural and functional changes in cortical and subcortical regions have been reported in behavioral variant frontotemporal dementia (bvFTD), however, a multimodal approach may provide deeper insights into the neural correlates of neuropsychiatric symptoms. In this multicenter study, we measured cortical thickness (CTh) and subcortical volumes to identify structural abnormalities in 37 bvFTD patients, and 37 age- and sex-matched healthy controls. For seed regions with significant structural changes, whole-brain functional connectivity (FC) was examined in a sub-cohort of N = 22 bvFTD and N = 22 matched control subjects to detect complementary alterations in brain network organization. To explore the functional significance of the observed structural and functional deviations, correlations with clinical and neuropsychological outcomes were tested where available. Significantly decreased CTh was observed in the bvFTD group in caudal middle frontal gyrus, left pars opercularis, bilateral superior frontal and bilateral middle temporal gyrus along with subcortical volume reductions in bilateral basal ganglia, thalamus, hippocampus, and amygdala. Resting-state functional magnetic resonance imaging showed decreased FC in bvFTD between: dorsal striatum and left caudal middle frontal gyrus; putamen and fronto-parietal regions; pallidum and cerebellum. Conversely, bvFTD showed increased FC between: left middle temporal gyrus and paracingulate gyrus; caudate nucleus and insula; amygdala and parahippocampal gyrus. Additionally, cortical thickness in caudal, lateral and superior frontal regions as well as caudate nucleus volume correlated negatively with apathy severity scores of the Neuropsychiatry Inventory Questionnaire. In conclusion, multimodal structural and functional imaging indicates that fronto-striatal regions have a considerable influence on the severity of apathy in bvFTD.

Airborne pollen grain detection from partially labelled data utilising semi-supervised learning - Benjamin Jin; Manuel Milling; Maria Pilar Plaza; Jens O. Brunner; Claudia Traidl-Hoffmann; Björn W. Schuller; Athanasios Damialis (Science of The Total Environment, 2023)

Modelling potential natural pest control ecosystem services provided by arthropods in agricultural landscapes - Marie Perennes; Tim Diekötter; Hannes Hoffmann; Emily A. Martin; Boris Schröder; Benjamin Burkhard (Agriculture, Ecosystems & Environment, 2023)

Barriers to evidence use for sustainability: Insights from pesticide policy and practice - Benjamin Hofmann; Karin Ingold; Christian Stamm; Priska Ammann; Rik I. L. Eggen; Robert Finger; Samuel Fuhrimann; Judit Lienert; Jennifer Mark; Chloe McCallum; Nicole Probst-Hensch; Ueli Reber; et al. (Ambio, 2023)
Calls for supporting sustainability through more and better research rest on an incomplete understanding of scientific evidence use. We argue that a variety of barriers to a transformative impact of evidence arises from diverse actor motivations within different stages of evidence use. We abductively specify this variety in policy and practice arenas for three actor motivations (truth-seeking, sense-making, and utility-maximizing) and five stages (evidence production, uptake, influence on decisions, effects on sustainability outcomes, and feedback from outcome evaluations). Our interdisciplinary synthesis focuses on the sustainability challenge of reducing environmental and human health risks of agricultural pesticides. It identifies barriers resulting from (1) truth-seekers’ desire to reduce uncertainty that is complicated by evidence gaps, (2) sense-makers’ evidence needs that differ from the type of evidence available, and (3) utility-maximizers’ interests that guide strategic evidence use. We outline context-specific research–policy–practice measures to increase evidence use for sustainable transformation in pesticides and beyond.

Economic costs of invasive alien ants worldwide - Elena Angulo; Benjamin D. Hoffmann; Liliana Ballesteros-Mejia; Ahmed Taheri; Paride Balzani; Alok Bang; David Renault; Marion Cordonnier; Céline Bellard; Christophe Diagne; Danish A. Ahmed; Yuya Watari; et al. (Biological Invasions, 2022)
Invasive ants are amongst the most destructive and widespread invaders across the globe; they can strongly alter invaded ecosystems and are responsible for the loss of native ant species. Several studies have reported that invasive ants can also lead to substantial economic costs. In this study, we search, describe and analyse 1342 reported costs of invasive ants compiled in the InvaCost database. Economic costs, reported since 1930 for 12 ant species in 27 countries, totalled US$ 51.93 billion, from which US$ 10.95 billion were incurred, and US$ 40.98 billion were potential costs (i.e., expected or predicted costs). More than 80% of total costs were associated with only two species, Solenopsis invicta and Wasmannia auropunctata ; and two countries, the USA and Australia. Overall, damage costs amounted to 92% of the total cost, mainly impacting the agriculture, public and social welfare sectors. Management costs were primarily post-invasion management (US$ 1.79 billion), with much lower amounts dedicated to prevention (US$ 235.63 million). Besides the taxonomic bias, cost information was lacking for an average of 78% of the invaded countries. Moreover, even in countries where costs were reported, such information was available for only 56% of the invaded locations. Our synthesis suggests that the global costs of invasive ants are massive but largely biased towards developed economies, with a huge proportion of underreported costs, and thus most likely grossly underestimated. We advocate for more and improved cost reporting of invasive ants through better collaborations between managers, practitioners and researchers, a crucial basis for adequately informing future budgets and improving proactive management actions of invasive ants.

Performance of the BD Phoenix CPO detect assay for detection and classification of carbapenemase-producing organisms - Laura Berneking; Anna Both; Benjamin Berinson; Armin Hoffmann; Marc Lütgehetmann; Martin Aepfelbacher; Holger Rohde (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
Increasing worldwide, prevalence of carbapenem-resistant gram-negative bacteria demands urgent a need for rapid detection and accurate identification of carbapenemases. The BD Phoenix CPO detect (PCD) assay possesses an in-built capacity for parallel susceptibility testing and detection of carbapenemases. Here, the ability of the assay to detect and classify carbapenemase production was tested in a collection of carbapenem-resistant Enterobacterales and non-fermentative gram-negative rods. The ability of the PCD assay to detect and classify carbapenemases was investigated in a collection of 194 clinical, carbapenem-resistant isolates ( Enterobacterales [ n = 65]; non-fermentative gram-negative rods [ n = 129]). AST results were compared to MICS determined by gradient diffusion to determine accuracy of the PCD assay. The accuracy of the PCD assay to detect carbapenemases was compared to the results of molecular isolate characterization using a LDT multiplex carbapenemase PCR assay. All 194 isolates classified as carbapenem-resistant by reference susceptibility testing were also classified correctly as CRO by the PCD assay. Performance analysis of the PCD assay to detect carbapenemase production revealed an overall sensitivity of 98.29% and specificity of 17.95% for the detection of carbapenemase production. For the classification of carbapenemases classes A, B, and D, the PCD correctly classified 79.17% Enterobacterales and 67.16% non-fermentative gram-negative rods. The PCD assay is a reliable tool for the detection of carbapenem resistance and allows for parallel analysis of carbapenemase production. However, while sensitivity is high, low specificity in carbapenemase detection and erroneous classification demands mandatory confirmation by alternative methods, especially in non-fermentative gram-negative bacteria.

Are north Australian floodplain ant communities comprised of a distinct fauna, or a subset of the broader savanna fauna? Implications for conservation - Benjamin D. Hoffmann; Florian Ivaldi; Abe Perez; Maud Laboual (Biodiversity and Conservation, 2019)

Tropical rainforest flies carrying pathogens form stable associations with social nonhuman primates - Jan F. Gogarten; Ariane Düx; Benjamin Mubemba; Kamilla Pléh; Constanze Hoffmann; Alexander Mielke; Jonathan Müller‐Tiburtius; Andreas Sachse; Roman M. Wittig; Sébastien Calvignac‐Spencer; Fabian H. Leendertz (Molecular Ecology, 2019)
Living in groups provides benefits but also incurs costs such as attracting disease vectors. For example, synanthropic flies associate with human settlements, and higher fly densities increase pathogen transmission. We investigated whether such associations also exist in highly mobile nonhuman primate (NHP) Groups. We studied flies in a group of wild sooty mangabeys ( Cercocebus atys atys ) and three communities of wild chimpanzees ( Pan troglodytes verus ) in Taï National Park, Côte d'Ivoire. We observed markedly higher fly densities within both mangabey and chimpanzee groups. Using a mark–recapture experiment, we showed that flies stayed with the sooty mangabey group for up to 12 days and for up to 1.3 km. We also tested mangabey‐associated flies for pathogens infecting mangabeys in this ecosystem, Bacillus cereus biovar anthracis ( Bc bv a ), causing sylvatic anthrax, and Treponema pallidum pertenue , causing yaws. Flies contained treponemal (6/103) and Bc bv a (7/103) DNA. We cultured Bc bv a from all PCR‐positive flies, confirming bacterial viability and suggesting that this bacterium might be transmitted and disseminated by flies. Whole genome sequences of Bc bv a isolates revealed a diversity of Bc bv a , probably derived from several sources. We conclude that flies actively track mangabeys and carry infectious bacterial pathogens; these associations represent an understudied cost of sociality and potentially expose many social animals to a diversity of pathogens.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Azaarenes in fine particulate matter from the atmosphere of a Chinese megacity - Benjamin A. Musa Bandowe; Hannah Meusel; Rujin Huang; Thorsten Hoffmann; Junji Cao; Kinfai Ho (Environmental Science and Pollution Research, 2016)

Can reforested and plantation habitats effectively conserve SW China’s ant biodiversity? - Zhixing Lu; Benjamin D. Hoffmann; Youqing Chen (Biodiversity and Conservation, 2016)

Worldwide ant invasions under climate change - Cleo Bertelsmeier; Gloria M. Luque; Benjamin D. Hoffmann; Franck Courchamp (Biodiversity and Conservation, 2015)

The end of Invasion Biology: intellectual debate does not equate to nonsensical science - Jacques Blondel; Benjamin Hoffmann; Franck Courchamp (Biological Invasions, 2014)

Eradication of populations of an invasive ant in northern Australia: successes, failures and lessons for management - Benjamin D. Hoffmann (Biodiversity and Conservation, 2011)

Yellow crazy ant (Anoplolepis gracilipes) invasions within undisturbed mainland Australian habitats: no support for biotic resistance hypothesis - Benjamin D. Hoffmann; Wolf-Christian Saul (Biological Invasions, 2010)

The neglected hypogeous fungus Hydnotrya bailii Soehner (1959) is a widespread sister taxon of Hydnotrya tulasnei (Berk.) Berk. & Broome (1846) - Benjamin Stielow; Ben Bubner; Gunnar Hensel; Babette Münzenberger; Peter Hoffmann; Hans-Peter Klenk; Markus Göker (Mycological Progress, 2010)

Ecological restoration following the local eradication of an invasive ant in northern Australia - Benjamin D. Hoffmann (Biological Invasions, 2010)

A potential antimicrobial treatment against ESBL-producing Klebsiella pneumoniae using the tellurium compound AS101 - Miriam Daniel-Hoffmann; Michael Albeck; Benjamin Sredni; Yeshayahu Nitzan (Archives of Microbiology, 2009)

Pisonia grandis monocultures limit the spread of an invasive ant—a case of carbohydrate quality? - Benjamin D. Hoffmann; Alice Kay (Biological Invasions, 2009)

An invasion revisited: the African big-headed ant (Pheidole megacephala) in northern Australia - Benjamin D. Hoffmann; Catherine L. Parr (Biological Invasions, 2008)